Industrial and small-scale biomass dryers: an overview - Murugan, P.; Dhanushkodi, S.; Sudhakar, K.; Wilson, Vincent H. (Tech Science Press, 2021)
The quality of the drying process depends mainly on the efficient use of thermal energy. Sustainable systems based on solar energy takes a leading role in the drying of agro-products because of low operating cost. However, they are limited in use during off–sun periods. Biomass dryer is one of the simplest ways of drying because of its potential to dry products regardless of time and climate conditions. The other benefit is that crop residues could be used as fuel in these systems. However, the major limitation of the dryer is unequal drying because of poor airflow distribution in the drying medium, which can be improved by integrating some design changes in the dryer. This review analyses the two types of biomass dryers: industrial biomass dryers and small biomass dryers for food product, along with their efficiency. Further, studies on technical, sustainability and economic aspects are expected to provide a greater understanding of biomass drying.